IMPLEMENTASI COMMUNITY DEVELOPMENT SECARA ONLINE PADA PROGRAM AMAN (AKU MUDA, AKU NYAMAN) WARRIOR TAHUN 2021 - Fathiyyah Nurul Izzah; Agus Suriadi (Tamilis Synex: Multidimensional Collaboration, 2025)
One indicator of achieving social welfare is developing oneself, which can be done by applying Community Development practices. Community Development, or in Indonesian, known as Community Development, is an effort towards a better life through activities and active participation that can develop the ability of groups or communities to be empowered. The COVID-19 pandemic and the Work From Anywhere phenomenon have pushed the world community to transition activities from alluring to daring, including community development practices that are carried out online. Online Community Development Practices can be a solution to the problem of limited face-to-face meetings and an opportunity to practice social services. The AMAN (I'm Young, I'm Comfortable) Warrior 2021 program by ECPAT Indonesia is one of the ongoing implementations of Online Community Development. This study aims to determine the stages of implementation and principles applied to the 2021 AMAN Warrior Program using a qualitative approach with a descriptive method. Data collection was carried out through interviews and documentation. The results of the findings of the stages of program implementation start from the stages of assessment, preparation, alternative program planning, formulation of action plans, implementation or implementation, and evaluation. Then, this research refers to the principles of Community Development put forward by Maryani and Nainggolan: equality, independence, participation, and sustainability. This program has implemented these four principles, but several must be improved. The hope is that Online Community Development practices can be disseminated by choosing the benefits of potential beneficiaries, namely those who can access the internet and have and can use qualified devices.